Causal relationship between private housing investment and economic growth: An empirical study. Issue 2 (6th June 2016) - Amidu, Abdul-Rasheed; Agboola, Alirat Olayinka; Musa, Mahmud
Abstract : Purpose: The paper aims to provide a better understanding of the interactions between housing investment and economic growth. In particular, the paper emphasizes the separate effects of private housing investment (PHI) on the aggregate economy using quarterly data in the UK from 1974 to 2015. This is important due to the relatively growing interest around the world, including the UK, in encouraging greater private housing investment as a way of boosting economic growth. Design/methodology/approach: The paper used the widely accepted and recognized econometric concepts of unit root, Granger causality and co-integration and provides tentative quantitative evidence of the causal and predictive effect of PHI and economic growth. Findings: The key finding is that the level of investment directed by individual and institution into the private housing sector is key to future development, and will strongly reduce economic performance volatility. Research limitations/implications: Given that this is a bivariate time series analysis of PHI and economic growth (proxy by gross domestic product), the conclusions of this paper need to treated with caution, as there are other potential variables that might be omitted to make the model more robust so as to reach a more conclusive result. Originality/value: This study complements existing literature, not only by providing new empirical evidence on the nexus between housing markets and the business cycle but also by being the pioneering attempt at examining the impact of PHI on the economy in the UK.